2016
DOI: 10.4236/jss.2016.46006
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Higher Moment Capital Asset Pricing Model for Karachi Stock Exchange (KSE)

Abstract: The purpose behind this study is to explore the relationship between expected return and risk of portfolios. It is observed that standard CAPM is inappropriate, so we introduce higher moment in model. For this purpose, the study takes data of 60 listed companies of Karachi Stock Exchange 100 index. The data are inspected for the period of 1 st January 2007 to 31 st December 2013. From the empirical analysis, it is observed that the intercept term and higher moments coefficients (skewness and kurtosis) are high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…The results of the study also demonstrate that there is a direct relation between stock returns and volatilities of the emerging and developed stock markets. These results are also consistent with previous research studies (Balsara et al, 2007;Kim et al, 2001;Lal, Mubeen, Hussain, & Zubair, 2016;Ribeiro et al, 2017;Slim et al, 2017;Trypsteen, 2017). Since the results indicate the mean reversion process in all the 12 emerging and developed markets, the returns of these markets revert back to their original past mean values after the certain time periods.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the study also demonstrate that there is a direct relation between stock returns and volatilities of the emerging and developed stock markets. These results are also consistent with previous research studies (Balsara et al, 2007;Kim et al, 2001;Lal, Mubeen, Hussain, & Zubair, 2016;Ribeiro et al, 2017;Slim et al, 2017;Trypsteen, 2017). Since the results indicate the mean reversion process in all the 12 emerging and developed markets, the returns of these markets revert back to their original past mean values after the certain time periods.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, enabling investors to forecast future returns on the basis of their historical value helping them in earning above average returns. Thus, supporting the studies of Chen and Hsu (2016), Vveinhardt et al (2016), Chaves and Viswanathan (2016), Lal et al (2016), Chaudhuri and Wu (2003), Riaz (2014), Poterba and Summers (1987), Malliaropulos and Priestley (1996), Mustafa and Ahmed (2013), Balvers et al (2000) etc. who also found the existence of mean reversion in different stock indices of the world.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 82%
“…However, the implication of time-varying estimates made them reject the hypothesis, which was concluding that mean reversions are not produced due to behavioral responses of investors. Similarly, Balsara et al (2007) while evaluating Shanghai and Shenzhen markets found that these markets fail to follow random walk, further found their study to support the findings of Lal et al (2016), Wang et al (2015), Balvers et al (2000), according to which, if stocks follow mean reversion theory then investors are likely to get profit from contrarian strategy.…”
Section: Literature Reviewmentioning
confidence: 74%
See 2 more Smart Citations